Qualidade da educação escolar: discursos, práticas e representações sociais - Oliveira, Maria Eliza Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present research aimed at understanding, by means of speeches collected in three spheres (education, academic, and school policies), the social representations regarding quality, and what they are or are not able to generate in actions carried out in public schools. Our analysis presupposes that the scientific practice must consider the multiple causes and the several players involved in order to understand the process of materializing educational public policies. Therefore, such approach has stimulated the use of new technologies so that it was possible to rebuild the reality from the comprehension of these multiple factors by mapping several speeches which constitute the scope of representations and social phenomena that influences the players to act in this everlasting game of conflicts and common senses which constitutes the always provisional reality we live. In this manner, we deal with social representations, the Collective Subject Discourse, and the Institutional Analysis. Theoretically, the first two enabled us to consider the speeches historical processes which generate practices to be transformed. With a myriad of possibilities resulted from this theoretical reference, we chose to deal with the Collective Subject Discourse which, besides offering elements to gather and analyze quantitative and qualitative data, has contributed to our access to what individuals say or to how they conceive the quality of school education. In our case, individuals are those who reproduce the speech of educational policy, and academic and school discourse. In addition, Institutional Analysis enabled us to understand, at the school scope, the repercussions of the analyzed speeches, tensing these discourses made by the school members and the practices they experienced. Among other analyzes presented in the course of this thesis, we reflect on the limited capacity of the speeches to have some influence on school practices and representations of...

A presente pesquisa percorre o objetivo de compreender, por meio de discursos coletados em três âmbitos (política educacional, acadêmico e escolar), quais são as representações sociais a respeito do tema qualidade e o que essas representações são ou não capazes de gerar nas ações empreendidas no interior das escolas públicas. Nossas análises pressupõem que o exercício científico deve considerar as múltiplas causas e a pluralidade de atores envolvidos para que seja possível compreender o processo de materialização das políticas públicas educacionais. A adoção desta abordagem incentivou, portanto, o uso de novas técnicas de modo que pudéssemos reconstruir a realidade a partir da compreensão desses múltiplos fatores, por meio do mapeamento de diversos discursos que formam o campo das representações e dos fenômenos sociais que influenciam a ação dos indivíduos neste jogo permanente de conflitos e consensos constitutivos da realidade, sempre provisória, em que nos encontramos. Desta forma, trabalhamos com as representações sociais, o Discurso do Sujeito Coletivo e a Análise Institucional. Teoricamente, as primeiras nos permitiram considerar os discursos como processos históricos que geram práticas que podem ser transformadas. Com uma variedade de possibilidades advinda deste referencial teórico, optamos por trabalhar com o Discurso do Sujeito Coletivo que, além de nos oferecer elementos para a coleta e a análise de dados qualitativos e quantitativos, contribuiu para que tivéssemos acesso ao que as pessoas dizem ou como as pessoas concebem a qualidade da educação escolar. Em nosso caso, as pessoas são aquelas que produzem o discurso da política educacional, o discurso acadêmico e da escola. Complementarmente, a Análise Institucional nos possibilitou compreender, no âmbito da escola, as repercussões dos discursos analisados, tensionando os discursos proferidos por esses integrantes da escola e as...
Keywords: Avaliação educacional; Politica e educação; Escolas públicas; Representações sociais; Education